Peacekeeping, private security and international human rights law: a review of UN policies - White, Nigel D. (Brill, 2014)
The un is used to ‘outsourcing’ or ‘contracting out’ its peacekeeping functions but, traditionally, this has been to states willing to contribute troops to an operation under overall un command and control. This model itself has created tensions between contributing states and the un. Given these conditions, and the fact that international law is traditionally seen as primarily applicable to states, it seems even more legally problematic that the un has, in recent years, started to outsource certain peacekeeping functions to the private sector. Inevitably, issues of applicable international laws, lines of responsibility and mechanisms for accountability, are less clear. In recent years the un has addressed this new practice by adopting a series of guidelines and polices on armed security contractors. The aim of this paper is to analyse these current un policies in the light of their compatibility with international law, particularly international human rights law.